ZONASI DAERAH BAHAYA LONGSOR DI KAWASAN GUNUNG TAMPOMAS KABUPATEN SUMEDANG, JAWA BARAT - -, Lucky Lukmantara (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Research area generally have a big slope. Based on Van Zuidam classification (1983), the research area can be divided into 3 angle class or slope: 1) area which have surging hilly morphology with of slope range from 25 - 35 %, 2) area which have precipitous hilly morphology with slope range from 35 - 90 %, and 3) area which have hilly morphology cut sharply or hilly very precipitous with slope 90 – 150 %Area which including into landslide-zone in generally reside at area which have precipitous hilly and surging hilly morphology, there are at group 2 and 3. Both of the area of compiler rock generally not yet lihtificated powerfully, water content is high enough especially in rain season and rock generally relative soften